Odpowiedź:
Proszę bardzo! :)
[tex]\frac{5x-3}{3x+6}*\frac{x^2+2x}{10x-6}=[/tex]
ZAŁOŻENIA!
1)
[tex]3x+6\neq 0\\\\3x\neq -6\ \ \ /:3\\\\x\neq -2[/tex]
2)
[tex]10x-6\neq 0\\\\10x\neq 6\ \ \ /:10\\\\x\neq \frac{6}{10}\\\\x\neq \frac{3}{5}[/tex]
Zatem:
D=R\{[tex]-2[/tex] ; [tex]\frac{3}{5}[/tex]}
[tex]\frac{5x-3}{3x+6}*\frac{x^2+2x}{10x-6}=\frac{5x-3}{3x+6}*\frac{x^2+2x}{2(5x-3)}=\frac{1}{3x+6}*\frac{x^2+2x}{2}=\frac{1}{3(x+2)}*\frac{x(x+2)}{2}=\frac{1}{3}*\frac{x}{2}=\frac{x}{6}[/tex]
Szczegółowe wyjaśnienie: